2020
DOI: 10.1002/ece3.6290
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild dynamics of understudied carnivores in a human‐altered landscape

Abstract: Mesocarnivores constitute a diverse and often abundant group of species, which are increasingly occupying hweigher trophic levels within multi‐use landscapes. Yet, we know relatively little about their interactions with each other, especially in human‐altered areas. Using camera trap data collected in a forestry concession in the Greater Gorongosa ecosystem of central Mozambique, we examined the spatiotemporal relationships and potential for intraguild competition among three understudied African carnivores: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Mozambique (Easter et al, 2020) and Kenya (Schuette et al, 2013), among others (Williams et al, 2018;Woodroffe, 2000). Land subdivision is a recent and ongoing phenomenon in the study area, with residential area increasing 670.26% from 1983 to 2007 in the region (Petitpas et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mozambique (Easter et al, 2020) and Kenya (Schuette et al, 2013), among others (Williams et al, 2018;Woodroffe, 2000). Land subdivision is a recent and ongoing phenomenon in the study area, with residential area increasing 670.26% from 1983 to 2007 in the region (Petitpas et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…We followed Meredith and Ridout (2018) to choose between the D1 or D4 estimator. We estimated confidence intervals using 10,000 bootstrap samples, and considered D > 0.80 to be a strong overlap (Easter et al, 2020).…”
Section: Overlap In Temporal Activitymentioning
confidence: 99%
“…Our a priori model (null model 2) indicated that similar and potentially competitive sympatric species should segregate in other ecological traits to avoid competition, producing more diffuse and complex interspecific interaction patterns, as Chesson (2000) suggested. In this sense, sympatry and coexistence may occur if similar sized species differentiate into one or more ecological traits, particularly primary food resources, activity time or other physical segregation (Easter et al, 2020; Godsoe et al, 2015; Kronfeld‐Schor & Dayan, 2003). For instance, the species pairs Herpailurus yagouaroundi and Nasua nasua , and Leopardus tigrinus and Nasuella olivacea are similar in size but differ in diet (Davis et al, 2018), whereas L. wiedii and H. yagouaroundi , Cerdocyon thous and Lycalopex gymnocercus (Di Bitetti et al, 2009, 2010) and some Mediterranean mesocarnivores (Vilella et al, 2020) exhibit different activity periods when they are sympatric.…”
Section: Discussionmentioning
confidence: 99%
“…The gathering of records over enough time provides a reasonable approximation to regional species pools [ 26 ], but species lists from distribution maps are of little use to track quick changes in species composition [ 27 ]. At the other end of the spectrum, field surveys accurately reporting changes in the composition of mammal communities often provide results only in the short term and at a local scale [ 28 , 29 ]. In between, efforts to monitor mammal communities on the intermediate spatiotemporal scales meaningful for detecting the effects of the drivers of global change are uncommon.…”
Section: Introductionmentioning
confidence: 99%